Slow Motion - Miller, Andie (My University, 2007)
The rationale of this work is a peripatetic exploration, both literally and intellectually: the form echoes the content. The creative work stands on its own, but the theoretical reflection contributes retrospectively to the work as part of this peripatetic process. The theoretical reflection picks up the theme, though more formally, in order to create one coherent project. I have aimed to create a dialogue between the theory and creative work on a road that goes both ways. If it appears that the section of theory devoted to the poets is disproportionately long compared to the rest of the work, this is because I discovered in the course of my exploration that poets seem more predisposed to wandering than others.
Student Number : 0310050V - MA research report - School of Literature and Language Studies - Faculty of Humanities
Keywords: pedestrian; walking; slowness; speed; autocentricity; peripatetic poets; crime; violence; personal essay; interview